Narasi Kebijakan di Era Disinformasi: Transformasi Pengambilan Keputusan Publik dalam Ekosistem Informasi Digital - Diryo Suparto; Kushandajani Kushandajani; Ida Hayu Dwimawanti; Tri Yuningsih; Ketut Purwantoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The dissemination of information through digital platforms has fundamentally transformed the processes of public policy formulation and decision-making. On the one hand, advances in communication technologies have enabled greater public participation and broader access to information. On the other hand, the proliferation of disinformation, narrative manipulation, and the fragmentation of the digital public sphere have the potential to affect the quality of government policies. This study aims to analyze the transformation of public decision-making processes within the digital information ecosystem characterized by the increasing production and distribution of disinformation. The research employed a descriptive qualitative approach through a systematic literature review by examining academic publications, policy documents, reports from international institutions, and national regulations related to digital information governance. The analysis was conducted using the policy narrative approach, the New Public Governance perspective, and policy network theory. The findings indicate that public decision-making is no longer dominated solely by government actors but is influenced by complex interactions among governments, digital platforms, mass media, civil society organizations, and interest groups. Disinformation plays a significant role in shaping public perceptions, altering policy agendas, and influencing the legitimacy of governmental decisions. Therefore, strengthening collaborative governance, enhancing digital literacy, and developing multi-stakeholder information verification mechanisms are essential to safeguarding democratic quality and improving the effectiveness of public policies in the digital era.